IMPROVING THE COMMUNITY ECONOMY THROUGH PRODUCTIVE ZAKAT (CASE STUDY OF THE AL-WUSTHO MOSQUE ZAKAT INSTITUTION, PRINGOMBO II VILLAGE, EAST LAMPUNG) - Khoiroh, Muflikhatul; Syakur, Abd.; Najiyah, Ashilatun; Solichah, Mas Amaliyatus (istinbath, 2025)
This article explains the zakat management pattern of the ʻāmil zakat of the Al-Wustho Mosque in Lampung. They developed an innovative, productive zakat model to empower the mosque community's economy. This empirical research relies on zakat management data excavated using in-depth interviews, documentation, and direct observation. The collected data was analyzed using analytical-synthetic thinking techniques, and as a result, it was found that the ʻāmil zakat of Al-Wustho mosque, Lampung, distributed zakat through the planning process; determination of mustaḥiq criteria and determination of mustaḥiq obligations after receiving productive zakat; implementation, determination of mustaḥiq that meets the requirements, transactional delivery of productive zakat between muzakkī and/or ʻāmil zakat and mustaḥiq based on mutually agreed provisions; After that, monitoring and evaluation were carried out, which resulted in a mustaḥiq performance report. With such a procedure, ʻāmil zakat in Lampung succeeded in improving the community's economy so that what was originally mustaḥiq then became muzakkī. The profits and benefits from the productive zakat capital from the muzakkī are partly donated to the mosque for the development and prosperity of the mosque's business, including the construction and expansion of the mosque, the cost of Friday prayers, free vegetable markets, and similar initiatives.